Athenry Castle, east interior wall of hall, window, base - O'Donovan, Danielle (My University, 2008)
Base of window angle shaft. Moulding from top down comprises: roll, bell, roll, roll, pinth.
E
Keywords: Architecture, Gothic -- Ireland; Galway (Ireland)--Buildings, structures, etc.; Medieval; roll moldings